(untitled) (Development Service Industry Management, 2025)
The article explores both theoretical foundations and practical manifestations of the transformation of business models in the entertainment industry under the profound influence of digital platforms and networked resources. In the context of the evolving digital economy, the research investigates emerging challenges faced by content producers, distributors, and consumers, highlighting the accelerating pace of change in technological environments and user preferences. It delves into the dynamics of how digital ecosystems are reshaping the logic of value creation, monetization, and market competition. The study introduces a structured typology of digital platforms—streaming (e.g., Netflix, Megogo), social (e.g., YouTube, TikTok), and gaming (e.g., Steam)—each representing distinct yet overlapping functions within the broader entertainment landscape. The role of these platforms in redefining traditional distribution channels, personalizing content delivery, and facilitating real-time user engagement is critically assessed. The importance of network effects, platform scalability, and data-driven decision-making are emphasized as core components of sustainable digital business strategies. Additionally, the article proposes analytical approaches to evaluate the mechanisms of value generation within digital ecosystems, incorporating concepts such as platform orchestration, user co-creation, and hybrid revenue models. Case studies from both global and Ukrainian markets are examined to demonstrate how entertainment companies successfully adapt to platform-based environments. These cases offer valuable insights into strategic flexibility, innovation capacity, and audience-centered content strategies. The conclusions underscore the imperative to reconsider conventional approaches to strategic management, innovation, and digital transformation within the entertainment industry. In a period marked by rapid technological advancement and changing consumption behaviors, the development of adaptive, platform-oriented business models becomes a critical success factor for sustained competitiveness.